Prevalence and Risk Factors of Polycystic Ovary Syndrome among Adolescent Girls in Sanden District: A Cross-Sectional Screening Study - Erna Yovi Kurniawati; Elin Noviasari (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2026)
Polycystic Ovary Syndrome (PCOS) is one of the most common endocrine disorders affecting women of reproductive age and often begins during adolescence. Early manifestations such as menstrual irregularities, acne, and metabolic disturbances may indicate an increased risk of PCOS. However, community-based evidence regarding PCOS risk among adolescents remains limited, particularly in developing countries. This study aimed to assess the prevalence of PCOS risk and identify associated factors among adolescent girls in Sanden District. This observational analytic study used a cross-sectional design in accordance with the STROBE Statement. A total of 32 adolescent girls aged 15–19 years were recruited using purposive sampling. Data were collected using a structured questionnaire assessing menstrual history, acne, hirsutism, and family history, along with anthropometric measurements to determine body mass index (BMI). Descriptive statistics were used to summarize participant characteristics, while bivariate analysis using the Chi-square test or Fisher’s exact test was performed to identify factors associated with PCOS risk. The results showed that 28.1% of participants were classified as being at risk of PCOS based on screening indicators. Menstrual cycle irregularity and BMI were significantly associated with PCOS risk (p < 0.05), whereas acne, hirsutism, and family history did not show statistically significant associations. These findings indicate that a considerable proportion of adolescent girls in Sanden District may already exhibit early indicators associated with PCOS risk. Early screening focusing on menstrual irregularities and BMI may support the early identification and prevention of reproductive and metabolic complications associated with PCOS.